The good earth [compact disc, unabridged] - Buck, Pearl S. (Pearl Sydenstricker), 1892-1973 (Blackstone Audio Inc., 2007)
"This Pulitzer Prize-winning classic tells the poignant tale of a Chinese farmer and his family in old agrarian China. The humble Wang Lung glories in the soil he works, nurturing the land as it nurtures him and his family. Nearby, the nobles of the House of Hwang consider themselves above the land and its workers; but they will soon meet their own downfall. Hard times come upon Wang Lung and his family when flood and drought force them to seek work in the city. The working people riot, breaking into the homes of the rich and forcing them to flee. When Wang Lung shows mercy to one noble and is rewarded, he begins to rise in the world, even as the House of Hwang falls" -- from publisher's web site.